Training and Employee Performance in Uganda: A Case of National Water and Sewerage Corporation Rukungiri District. - Twongyeirwe, Uster (Kabale University, 2024)
This study investigated the relationship between Training and Employee Performance in Uganda considering the case of the National Water and Sewerage Corporation-Rukungiri District. The study's specific goals were to examine the relationship between on-the-job training and employee performance, determine the relationship between off-the-job training and employee performance, and find out the challenges that affect training and employee performance at NWSC Rukungiri District. Senior human resource managers and managerial and technical level personnel made up the sample of 96 respondents that the study studied using a cross-sectional and descriptive survey design. Self-administered questionnaires and interviews were used to gather primary data,.Statistical Package for Social Sciences (SPSS 26.0), descriptive statistics, linear regression, and analysis of variance (ANOVA) were used to analyze quantitative data. Content exploration and thematic integration with the quantitative results were part of the qualitative data analysis process. The research findings indicate a statistically significant positive relationship (r=0.772, p<0.01) between on-the-job training and employee performance at NWSC-Rukungiri District. The study also found out that off-the-job training and employee performance at NWSC-Rukungiri District had a moderately significant positive relationship (r=0.683, p<0.01). The study further established that on-the-job training accounts for 59.7%, while off-the-job training accounts for 46.0% of employee performance. The study further established that both on-the-job and off-the-job training methods are significant predictors of employee performance (p<0.05). However, on-the-job training is a stronger predictor of employee performance (β=0.593, p<0.05) than the job training method (β=0.477, p<0.05). The study also established that training generally accounts for 69.8% of the employee performance at NWSC Rukungiri District. The study established that the main challenges to training at NWSC-Rukungiri District are lack of enough funds, use of inappropriate training technology, and lack of training feedback. The study concluded that improving training through both on-the-job and off-the-job methods would improve employee performance. It was recommended that in the attempt to improve employee performance, training should be improved through both on-the-job and off-the-job methods although priority should be given to on-the-job training approaches, while the identified challenges to training should be addressed to enhance the effectiveness of training on employee performance.